LncRNA SNHG12 ameliorates bupivacaine-induced neurotoxicity by sponging miR-497–5p to upregulate NLRX1. (29th March 2022) - Sun, Lijie; Yuan, Ru
Long non-coding RNA (lncRNA) small nucleolar RNA host gene 12 (SNHG12) has been reported to participate in the regulation of various nervous system disorders. Bupivacaine (BV), a commonly used local anesthetic, could generate neurotoxicity in neurons. This work intended to investigate the role and specific mechanism of SNHG12 in BV-induced neurotoxicity. In this study, we established an in vitro cell model of BV-induced neurotoxicity by exposing human neuroblastoma cells (SH-SY5Y) to BV. It was found that SNHG12 and NLRX1 levels were gradually downregulated, while miR-497–5p enrichment was upregulated accordingly with the increase of BV concentration. As indicated by functional assays, SNHG12 overexpression promoted cell viability but inhibited cell apoptosis and oxidative stress in BV-treated SH-SY5Y cells. In addition, it was identified that SNHG12 directly targeted miR-497–5p and attenuated BV-induced neurotoxicity via interaction with miR-497–5p. Besides, it was confirmed that SNHG12 could upregulate NLRX1 expression by absorbing miR-497–5p. Moreover, miR-497–5p decreased cell viability and induced cell apoptosis and oxidative stress, which was partly reversed by NLRX1 upregulation. In conclusion, our findings indicated that SNHG12 might relieve BV-associated neurotoxicity by upregulating NLRX1 via miR-497–5p in vitro, providing novel clues and biomarkers for the treatment and prevention of BV-associated neurotoxicity.